Development of a portable fiber optic sensor prototype for pesticides residue measurement / Khairul Anuar Shafie - Shafie, Khairul Anuar (2008)
In recent years, Malaysian farmers lost million of ringgit due to suspension of their product from being exported to our neighboring countries. This is due to lack of monitoring action being taken to control the pesticides residue used in crops especially in vegetables and fruits. There are a few measuring instruments that can be used to measure the pesticide residue , but due to the incompetent in technical skills of the farmers and also financial constraint , the in-house implementation of the system is restricted. In this research, a portable fiber optic sensor measuring instrument has been developed. The prototype consists of three sections that are opto-electronic system, electronic system, and fiber optic probe. The probe consists of 32-core fiber optic that has been bifurcated into three parts. The fiber optic probe will be used as a light signal transmission to the samples. In previous research , the complexity of the timer and control circuitry is one of the problem arises in designing the instrument. By then, the timer and control circuitry that use a combination of crystal oscillator and logic gate components was replaced with Peripheral Interface Controller (PIC) microcontroller (MCU). The PIC MCU can reduce the number of components and pin count, thus producing small and portable prototype with competitive performance when compared to other commercially available instrument. The instrument is also introduced with calibration circuit. The circuit can be used to calibrate the prototype with standard samples , thus reduce the zero-and-span problem. For the application of fiber optic sensor , the prototype will measure the color changes of the parameters. The parameters that will be determined are a standard color solution that will represent the pesticides residue concentration. The solution consists of known amount of pesticide residue which inhibit with enzyme in free solution. By adding a color reagent , a yellow color will produce based on the concentration of the pesticides residue. The darker the yellow color produce, the less amount of pesticide concentration in the solution. In this research , the characterization of bioassay for pesticide concentration has been successfully achieved by using fiber optic sensor prototype. The result from the fiber optic sensor measuring instrument is comparable with a spectrophotometer.